FORAGE PREFERENCE OF CAMEL CALVES (C AMELUS DROMEDARIUS) I N EASTERN ETHIOPIA - M. B. Chimsa; Y. Y. Mummed; M.Y Kurtu; M.U. Leta; A. Hassen; B.S. Gemeda (Journal of Animal and Plant Sciences, 2013)
A study on forage preference of Camel calves from 6 to 12 months of age was conducted in eastern Ethiopia. Data were collected at an interval of 50 minutes for each calf for 15 consecutive days in dry and wet season. Based on the observation, calves commonly selected 13 plant species in the dry season and 15 plant species in the wet season. The top 10 plant species preferred by calves accounted for about 99% and 94% of the total browsed forage species during the dry and wet season, respectively. Opuntia ficus-indicus was the most frequently browsed forage species both in the wet (37%) and dry (41%) seasons. The second frequently browsed species in dry season were Lantana camara (15.09%) and Becium species (15.09%) and in wet season Becium species (13.08%). The crud protein (CP) content of mixed plant species browsed by the calves in the dry and wet season was 13.8 and 27.7 %, respectively. On average calves spent 79.51 + 14.83% of their time on browsing during the dry and wet season in the present study. Relatively more time spent on browsing in wet season (82.11 + 9.74%) compared to dry season (76.91 + 19.92%). From the study it was concluded that number of commonly preferred forage species of calves were less than number reported for mature Camels. Calves selected for feed with lower CP content in dry season compared to wet season. Moreover, time spent browsing was relatively lower in dry season compared to wet season. It is therefore, recommended that further study will be suggested to know how much the requirement of the calves can be satisfied from the liquid milk suckled from the dams and solid feed available in the area in order to supplement the calves strategically.
Keywords: Camel calves; Forage preference; Time spent on browsing; Chemical composition of forage